State language policy and linguistic practice of Kazakhstani students in the context of sociological measurements (The Journal of Psychology and Sociology, 2022)
The article is the result of the research on the assessment of the language policy of the Republic of Kazakhstan, implemented within the framework of the state order. The aim of the research was to study the everyday speech practices of the students at secondary schools and colleges of Kazakhstan in the context of three ethnic groups – Kazakhs, Russians and other ethnic groups, including small ethnic groups of the country. The main directions of the research are to determine the level of proficiency of three ethnic groups of young people in the state and Russian languages, the scope of application of these languages in the ethnic dimension and analysis of language practices and strategies of young people. Methodology of research – a quantitative method of sociology, mass questionnaire poll, the sample volume – 1000 pupils from 14 regions of RK and 3 cities of republican value, at the age from 12 till 17 years old. The main results of the research are the following: the state language prevails in the language practice of representatives of the Kazakh ethnos, and its sphere of application is limited to family and educational objects, in the language practice of the country’s youth one-sided, non-regressive bilingual- ism prevails, demonstrating the dominance of the Russian language and its active use in different spheres of public life. The practical value of the work is expressed in the use of the data for the improvement of the language policy of the republic and the application of the research results in the development of lectures by teachers on relevant topics.Key words: bilingualism, spheres of language use, Kazakh youth.